Uji Aktivitas Antioksidan Ekstrak Etanol 96% Daun Kelor (Moringa oleifera Lam.) Menggunakan Metode DPPH (2,2-difenil-1-pikrilhidrazil) - Okkyana Kusuma Putri; Poppy Indrianti; Alfian Fauzi; Hafizh Baihaqi (PT Bukuloka Literasi Bangsa, 2026)
Antioxidants are compounds that can slow down or prevent damage caused by free radicals. A continuous increase in free radicals in the body can trigger degenerative diseases such as cancer, diabetes, inflammation, and cardiovascular disease. Antioxidants can be obtained from both natural and synthetic sources. One natural source that can be utilized is moringa leaves. The antioxidant compounds found in moringa leaves include polyphenols and flavonoids. This study aims to determine the antioxidant activity of a 96% ethanol extract of moringa leaves (Moringa oleifera Lam) using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The instrument used in the testing was a UV-Vis spectrophotometer, while the materials used were moringa leaf extracts obtained via the maceration method at concentrations of 20, 40, 60, 80, and 100 ppm, with vitamin C serving as the positive control. Based on the research results, it was concluded that the 96% ethanol extract of moringa leaves (Moringa oleifera Lam) possesses antioxidant activity with an IC50 value of 49.12 ppm, indicating very strong antioxidant activity. Keywords: Free Radicals, Moringa Leaves, Antioxidant Activity Test, DPPH